2019
DOI: 10.1111/ijfs.14463
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of spinach by isochoric (constant volume) freezing

Abstract: Efforts are currently directed towards improving the quality of vegetables after freezing and thawing. One of the methods under investigation is isochoric freezing. In this study, we evaluated isochoric freezing for preserving the quality of baby-leaf spinach. We compared the properties of thawed spinach frozen to À4°C in an isochoric system with those of fresh spinach, thawed spinach frozen to À4°C in an isobaric system and thawed spinach that were commercially frozen. Spinach leaves frozen under isobaric con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
1
18
1
9
Order By: Relevance
“…In contrast, the entire amount of water will be frozen at this temperature in an isobaric system. Previous studies have evaluated the effects of isochoric freezing on various food products and demonstrated that isochoric freezing can result in improved physical and nutritional qualities of frozen foods (Bilbao‐Sainz et al., 2018, 2019) as well as substantial energy savings (Powell‐Palm and Rubinsky, 2019). In this study, we examined the effects of isochoric freezing on the physical and nutritional properties of peeled and diced potato cubes and compared the results with individual quick freezing (IQF) currently used in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the entire amount of water will be frozen at this temperature in an isobaric system. Previous studies have evaluated the effects of isochoric freezing on various food products and demonstrated that isochoric freezing can result in improved physical and nutritional qualities of frozen foods (Bilbao‐Sainz et al., 2018, 2019) as well as substantial energy savings (Powell‐Palm and Rubinsky, 2019). In this study, we examined the effects of isochoric freezing on the physical and nutritional properties of peeled and diced potato cubes and compared the results with individual quick freezing (IQF) currently used in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Isochoric cryopreservation—the cryopreservation process in a sealed rigid container—has been presented as a promising approach for the preservation of biological materials in low temperatures, with potential benefits to tissue and organ banking [ 1 3 ], as well as to the food industry [ 4 , 5 ]. From a thermodynamics perspective, the term isochoric refers to an ideal process occurring within constant-volume boundaries and is used interchangeably with isovolumetric and isometric in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, pressure-related damage has been reported in tissues and organs stored under prolonged HSZ isochoric conditions [ 13 , 16 ]. Similarly, the benefits of HSZ isochoric preservation of food products have also been demonstrated, using additives such as saline solution, sugars, and some common CPAs, which resulted in improved retention of color, flavor and nutritional values [ 4 , 5 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, TSP content can also be decreased during preservation. We came to know about this when spinach leaves were preserved byBilbao-Sainz, Sinrod, Dao, et al (2020) in isochoric…”
mentioning
confidence: 99%
“…have been reported in various literatures of isochoric frozen fruit and vegetable such as in tomato(Bilbao-Sainz et al, 2021); fish muscles(Năstase et al, 2017); Tilapia (Oreochromis aureus) Fillet; processed potato(Bilbao-Sainz, Zhao, Takeoka, et al, 2020); spinach (Bilbao-Sainz, Sinrod, Dao, et al, 2020); sweet cherry(Bilbao-Sainz, Sinrod, Dao, et al, 2020). As a description, morphological variations in fresh, isochoric, isobaric, and commercially available frozen spinach leaves were compared byBilbao-Sainz. Sinrod, Dao, et al (2020) and shown in Figure6af.…”
mentioning
confidence: 99%